2019
DOI: 10.1080/13696998.2019.1606002
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of denosumab for the prevention of skeletal-related events in patients with multiple myeloma in four European countries: Austria, Belgium, Greece, and Italy

Abstract: Aim: The approved indication for denosumab (120 mg) was expanded in 2018 to include skeletalrelated event (SRE) prevention in patients with multiple myeloma (MM). Therefore, a cost-effectiveness analysis was conducted comparing denosumab with zoledronic acid (ZA) for SRE prevention in patients with MM from the national healthcare system perspective in a representative sample of European countries: Austria, Belgium, Greece, and Italy. Methods: The XGEVA global economic model for patients with MM was used to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 62 publications
1
20
0
1
Order By: Relevance
“…Treatments that reduce the incidence of SREs, therefore, have the potential to reduce the cost burden to healthcare services and society. While the acquisition cost of the monoclonal antibody denosumab is higher than that of generic bisphosphonates, cost-effectiveness analysis has shown that incremental costs per quality-adjusted life year (QALY) and per SRE avoided with denosumab are well below willingness-to-pay thresholds, and thus denosumab can be considered cost effective for prevention of SREs [111,112]. In an alternative costeffectiveness analysis conducted based on US data, denosumab and ZA were associated with similar QALYs gained, and thus the authors concluded that the lower cost of ZA made it the optimal treatment [113].…”
Section: Rankl-targeted Monoclonal Antibodies: Denosumabmentioning
confidence: 99%
“…Treatments that reduce the incidence of SREs, therefore, have the potential to reduce the cost burden to healthcare services and society. While the acquisition cost of the monoclonal antibody denosumab is higher than that of generic bisphosphonates, cost-effectiveness analysis has shown that incremental costs per quality-adjusted life year (QALY) and per SRE avoided with denosumab are well below willingness-to-pay thresholds, and thus denosumab can be considered cost effective for prevention of SREs [111,112]. In an alternative costeffectiveness analysis conducted based on US data, denosumab and ZA were associated with similar QALYs gained, and thus the authors concluded that the lower cost of ZA made it the optimal treatment [113].…”
Section: Rankl-targeted Monoclonal Antibodies: Denosumabmentioning
confidence: 99%
“…infusion of bisphosphonates during the coronavirus disease 2019 (COVID‐19) pandemic in order to reduce hospital visits or the length of hospital stay 66 . Economic models have also shown that denosumab is a cost‐effective treatment both in Europe 67 and the USA 68 …”
Section: Which Bone‐modifying Agent To Choose?mentioning
confidence: 99%
“…times the country's gross domestic product (GDP) per capita to assess interventions' cost-effectiveness. [27][28][29] Nevertheless, no research has shed light on whether this threshold is appropriate for decision making or not. Moreover, related Greek studies that measure WTP per QALY (WTP/QALY) estimates have focused on discrete interventions/drugs for specific diseases, [28][29][30][31] and therefore WTP/QALY values refer to specific patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Nevertheless, no research has shed light on whether this threshold is appropriate for decision making or not. Moreover, related Greek studies that measure WTP per QALY (WTP/QALY) estimates have focused on discrete interventions/drugs for specific diseases, [28][29][30][31] and therefore WTP/QALY values refer to specific patient populations. A previous Greek study 18 estimated a WTP/QALY value for an outpatient population, but study findings cannot be generalized to the Greek population.…”
Section: Introductionmentioning
confidence: 99%